2007
DOI: 10.1007/s00421-007-0400-4
|View full text |Cite
|
Sign up to set email alerts
|

Protein requirements in male adolescent soccer players

Abstract: Few investigations have studied protein metabolism in children and adolescent athletes which makes difficult the assessment of daily recommended dietary protein allowances in this population. The problematic in paediatric competitors is the determination of additional protein needs resulting from intensive physical training. The aim of this investigation was to determine protein requirement in 14-year-old male adolescent soccer players. Healthy male adolescent soccer players (N = 11, 13.8 +/- 0.1 year) partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 24 publications
0
34
0
3
Order By: Relevance
“…In her work, Dolins indicated that, for physically active women, a dose of 1.2 g of protein/kg body mass/day is sufficient to maximize sporting achievements [53]. Boisseau et al stated that the Estimated Average Requirement (EAR) for football players should be 1.2 g/kg body mass/day, while the Recommended Dietary Allowances (RDA) is 1.4 g/kg body mass/day [54]. Although most studies and recommendations have referred to men or are targeted at athletes as a whole, protein recommendations are adequate for both men and women who train football [55].…”
Section: Proteinsmentioning
confidence: 99%
“…In her work, Dolins indicated that, for physically active women, a dose of 1.2 g of protein/kg body mass/day is sufficient to maximize sporting achievements [53]. Boisseau et al stated that the Estimated Average Requirement (EAR) for football players should be 1.2 g/kg body mass/day, while the Recommended Dietary Allowances (RDA) is 1.4 g/kg body mass/day [54]. Although most studies and recommendations have referred to men or are targeted at athletes as a whole, protein recommendations are adequate for both men and women who train football [55].…”
Section: Proteinsmentioning
confidence: 99%
“…To the best of our knowledge, only two studies have assessed this parameter by determining the nitrogen balance of adolescent male soccer players [31,32]. Those authors concluded that the protein requirements of these adolescents were above the recommended daily allowance of non-active counterparts, and reported a positive nitrogen balance from a mean protein intake of 1.57 g/kg BM.…”
Section: Nutritional Intake and Eating Habits Of Soccer Playersmentioning
confidence: 99%
“…The objectives of these guidelines are to optimize performance during training and competition, improve and accelerate recovery, achieve and maintain an optimal body weight and physical condition, and minimize the risk of injury and illness [31,32,33,34,35,36,37]. Recommended macronutrient intake has traditionally been expressed as a percentage of total energy intake (% energy).…”
Section: Introductionmentioning
confidence: 99%
“…Boisseau et al . [13] conducted a nitrogen balance study on a group of adolescent soccer players and reported a protein need of 1.4 g/kg·day. Daily recovery and fuel needs for athletes with a moderate volume exercise program requires a carbohydrate intake of 5 to 7 g/kg·body mass [14].…”
Section: Introductionmentioning
confidence: 99%